Interhemispheric Connections between the Primary Visual Cortical Areas via the Anterior Commissure in Human Callosal Agenesis - van Meer, Nathalie; Houtman, Anne C.; Van Schuerbeek, Peter; Vanderhasselt, Tim; Milleret, Chantal; ten Tusscher, Marcel P. (Frontiers in Systems Neuroscience, 2016)
Aim: In humans, images in the median plane of the head either fall on both nasal hemi-retinas or on both temporal hemi-retinas. Interhemispheric connections allow cortical cells to have receptive fields on opposite sides. The major interhemispheric connection, the corpus callosum, is implicated in central stereopsis and disparity detection in front of the fixation plane. Yet individuals with agenesis of the corpus callosum may show normal stereopsis and disparity vergence. We set out to study a possible interhemispheric connection between primary visual cortical areas via the anterior commissure to explain this inconsistency because of the major role of these cortical areas in elaborating 3D visual perception. Methods: MRI, DTI and tractography of the brain of a 53-year old man with complete callosal agenesis and normal binocular single vision was undertaken. Tractography seed points were placed in both the right and the left V1 and V2. Nine binocular individuals with both an intact corpus callosum and normal binocularity served as controls. Results: Interhemispheric tracts through the anterior commissure linking both V1 and V2 visual cortical areas bilaterally were indeed shown in the subject with callosal agenesis. All other individuals showed interhemispheric visual connections through the corpus callosum only. Conclusion: Callosal agenesis may result in anomalous interhemispheric connections of the primary visual areas via the anterior commissure. This It is proposed here that these connections form as alternative to the normal callosal pathway and may participate in binocularity.